Fiscal Stimulus to the Rescue? : Short-Run Benefits and Potential Long-Run Costs of Fiscal Deficits - Laxton, Douglas (IMF Working Papers; Working Paper ;, 2009)
This paper uses the IMF's Global Integrated Monetary and Fiscal Model to compute shortrun multipliers of fiscal stimulus measures and long-run crowding-out effects of higher debt. Multipliers of two-year stimulus range from 0.2 to 2.2 depending on the fiscal instrument, the extent of monetary accommodation and the presence of a financial accelerator mechanism. A permanent 0.5 percentage point increase in the U.S. deficit to GDP ratio raises the U.S. tax burden and world real interest rates in the long run, thereby reducing U.S. and rest of the world output by 0.3-0.6 and 0.2 percent, respectively.